Managing Change Through Leadership Discourse: An Experience in the Surgical Ward - Ahmad, Hafiz Naweed; Malik, Wusqa Sultana; Malik, Fakiha Sultana (Biological and Clinical Sciences Research Journal, 2025)
Leadership is a phenomenon that develops in social interaction. This phenomenon is expressed at individual level when a leader with his clearly stated vision, leadership qualities, and style of working, leads the followers to work for the common goals, which are usually ethically motivated and aimed to benefit human life and experience. Leadership governs at the organizational level when different institutions and instruments of the organization work in coherence with meaningful concerted interaction, sharing their roles and responsibilities to produce the best possible results aligned with the ‘vision statement’ of the organization. Leadership is not just limited to those who are in a formal position of authority, but it is the use of power and influence to create a positive change that can benefit humans and society by alleviating their difficulties, worries, and anxiety. Objectives: To create a change through leadership discourse in order to reduce the difficulties of patients and their attendants regarding laboratory investigations. Methods: A change project was accomplished in the surgical ward of Bahawal Victoria Hospital, Bahawalpur, Pakistan, during September-November 2017, to introduce a facilitated method of handling patients’ laboratory samples. Transformational leadership style and SSM methodology were adopted as the change management model. The outcome of the project was studied through mixed methods. Quantitative method was used through specific questions from trainee doctors, house officers, and nurses. And the qualitative method was applied through focus group discussions with the same groups. Results: All the participants unanimously agreed on the ‘need’ for change. And their majority opined that the method was appropriate and deemed the change successful. However 25 % to 33% participants in stakeholders’ groups expressed their concerns over the methodology and long-term success of change. Qualitative exploration revealed the reasons underpinning their concerns.